Writing training materials that work : how to train anyone to do anything - Foshay, Wellesley R.; Silber, Kenneth H.; Stelnicki, Michael B. (New York : Jossey-Bass / Pfeiffer, 2003)
Business
2004-10-17
Keywords: Training; Training manuals; Employees; Teaching